Allometric equation for estimating the aboveground biomass of Gentiana algida, Gentiana macrophylla in Mongolia (Mongolian Journal of Botany, 2024)
The traditional method of calculating plant biomass involves harvesting plant yields and measuring the weight difference between wet and dry samples. However, this method can have negative consequences for rare and extremely rare species of plants. Therefore, we are studying the method of calculating biomass using measurements such as the diameter, height and cover of plant bases. In the Khangai and Khentii provinces of Mongolia, the necessary data was collected and processed within the framework of creating an allometric formula for calculating the above-ground biomass of 2 species of the genus Gentiana (Gentiana algida, Gentiana macrophylla). These include: measuring the basal length and width of 2 species of plants, the total height, and above-ground biomass. An allometric formula for calculating above-ground biomass using collected data was developed. This method has the potential to supplant clengurrent methods, as the complete removal aboveground biomass through cutting. According to the research results, out of the total 16 allometric equations used to calculate the biomass of two species of Gentiana algida species, R2 was 0.634 equation Ỳ = 0.341+0.001*(D^2)*H. Comparing RMSE and AIC, the following equation lnỲ= -3.768+1.229*ln(D)+0.482*ln(H) showed a high statistical fit. But for Gentiana macrophylla species, the allometric equation lnỲ= -4.152+1.014*ln(D)+0.707*(H) showed the best relationship for predicting aboveground biomass. From these allometric equations, it can be seen that plant height (H) and diameter of the base (D) are the most relevant parameters for the above ground biomass of the sedge species, and with the help of repeated measurements of these parameters, it is possible to determine the biomass of the individualӨлчир дэгд (Gentiana algida), томнавчит дэгд (Gentiana macrophylla)-ийн биомассыг аллометрийн тэгшитгэлээр тооцохХураангуй. Ургамлын биомассыг тооцоолох уламжлалт арга нь ургамлын газрын гадарга дээрх хэсгийг хайчилж, хатааж жинлэх юм. Энэ арга нь нэн ховор, ховор зүйл ургамлуудын нөөцийг хомсдуулах бөгөөд мөн эдийн засгийн сөрөг нөлөөтэй. Монгол орны зарим зүйл мод болон сөөг ургамлын биомассыг тооцох аллометрийн тэгшитгэлүүд зохиогдсон боловч өвслөг ургамал дээр хараахан зохиогдоогүй байна. Тиймээс бид Дэгдийн төрлийн хоёр зүйл (Gentiana algida- Өлчир дэгд, Gentiana macrophylla-Томнавчит дэгд) ургамлын газрын дээрх биомассыг тооцоолох аллометрийн тэгшитгэл зохиох зорилгоор Монгол орны Хангай болон Хэнтийн ургамал-газарзүйн тойргоос нийт хоёр зүйлийн 218 бодьгалын суурийн урт, суурийн өргөн, өндөр, газрын дээрх биомасс зэрэг өгөгдлүүдийг цуглуулж, боловсруулалт хийн, газрын дээрх биомасс тооцоолох хамгийн тохиромжтой аллометрийн тэгшитгэлийг гаргав. Судалгааны үр дүнгээс харахад Дэгдийн төрлийн хоёр зүйл ургамлын биомасс тооцоолоход ашигласан нийт 16 аллометрийн тэгшитгэлээс Gentiana algida зүйлийн хувьд R2 хамгийн их 0.634 тэгшитгэл Ỳ= 0.341+0.001*(D^2)*H байсан. RMSE болон AIC-ийг харьцуулан бодоход дараах тэгшитгэл lnỲ=-3.768+1.229*ln(D)+0.482*ln(H) статистикийн хувьд өндөр нийцтэй байв. Харин Gentiana macrophylla зүйлийн хувьд lnỲ=-4.152+1.014*ln(D)+0.707*(H) гэсэн аллометрийн тэгшитгэл газрын дээрх биомассыг урьдчилан таамаглах хамаарлыг хамгийн сайн үзүүлсэн. Эдгээр аллометрийн тэгшитгэлээс харахад дэгдийн төрлийн газрын дээд биомассд хамгийн өндөр хамааралтай үзүүлэлтүүд нь ургамлын өндөр (H) болон суурийн диаметр (D) байгаа ба эдгээр үзүүлэлтүүдийн олон давталттай хэмжилтийн тусламжтайгаар тухайн бодгалийн биомассыг тогтоох боломжтой байна.Түлхүүр үг: Өлчир дэгд, Томнавчит дэгд, газрын дээрх биомасс, аллометрийн тэгшитгэл